The Potential of Hand Wash Liquid from Galam (Melaleuca cajuputi) - Muh Azhari; Sri Marlina (Center for Journal Management and Publication, 2022)
Galam (Melaleuca cajuputi) is a typical plant of the peat environment in Central Kalimantan. Galam is used by the community to meet the needs of boards, bridges and other functions. Utilization of Galam (Caulis) causes the accumulation of certain biomass such as leaves. Waste of Leaf Galam can be used to isolate the volatile through the distillation process. These essentials can be used as active ingredients for making liquid hand soap. The liquid hand soap can be an alternative to hand washing soap in the era of the COVID-19 pandemic. The results showed that the organic compounds contained in the volatile using the Gas Chromatography Mass Spectrometry (GCMS) method, such as 1,8-Cineole, 1-Phellandrene, 2 Beta-Pinene, 3-Cyclohexen-1-ol, 8-Cineole, Alpha Terpinene , Alpha-Humulene, Alpha-Selinene, Alpha-Terpinolene, Alpha-Thujene, Benzene, Beta Fenchyl Alcohol, Beta –Selinene, Beta-Elemene, Beta-Myrcene, DI-Limonene, Gamma-Terpinene, Ledene, R(+)- Limonene, and Trans-Caryophyllene. Seeing the content of volatile organic compounds in galam leaf waste, hand soap from galam leaf waste has the potential to inhibit the activity of microorganisms.